2021
DOI: 10.1177/09673911211020601
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites based on biocompatible polymers and graphene oxide for antibacterial coatings

Abstract: Recently, antibacterial coatings based on graphene oxide (GO) nanocomposites have attracted many studies around the world. The use of polymers as the matrices of GO nanofillers in the nanocomposites has been explored to produce efficient coatings against bacteria. One of the most prospective applications is the incorporation of GO into biocompatible polymers, which can produce antibacterial coatings. Here, recent progresses on the antibacterial coatings of nanocomposites based on biocompatible polymers and GO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 99 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…Incorporation of inorganic bioactive fillers, including calcium phosphates [ 53 , 87 ], silicate [ 88 ], BG [ 89 ], CNT [ 90 ], and graphene [ 91 ], into polymeric substrates has been prepared with an emphasis on the fabrication of hybrid biocomposites with tunable stiffness, as well as the adjustment of biological performance. As one of the primary components of bone ECM, calcium phosphates, mainly in the form of HAp [ 53 , 92 ], have been widely used as osteoinductive fillers in bone substrates due to their high strength and outstanding osteoconductivity.…”
Section: Strategies To Tune the Stiffness Of Engineering-based Substr...mentioning
confidence: 99%
“…Incorporation of inorganic bioactive fillers, including calcium phosphates [ 53 , 87 ], silicate [ 88 ], BG [ 89 ], CNT [ 90 ], and graphene [ 91 ], into polymeric substrates has been prepared with an emphasis on the fabrication of hybrid biocomposites with tunable stiffness, as well as the adjustment of biological performance. As one of the primary components of bone ECM, calcium phosphates, mainly in the form of HAp [ 53 , 92 ], have been widely used as osteoinductive fillers in bone substrates due to their high strength and outstanding osteoconductivity.…”
Section: Strategies To Tune the Stiffness Of Engineering-based Substr...mentioning
confidence: 99%
“…The antibacterial/antiviral behavior of graphene oxide has been previously reported, 26 and the main advances are summarized in Table 1. Recently, with the emergence of the COVID-19 pandemic, GO application as antivirals has broadly 27 showed that GO can exhibit significant antiviral properties even at a low concentration (1.5 μg/mL), which may be attributed to the negative charge and nanosheet structure, which was further demonstrated for SARS-CoV-2 variants by other authors.…”
Section: Antiviral Properties Of the Masksmentioning
confidence: 99%
“…The antibacterial/antiviral behavior of graphene oxide has been previously reported, 26 and the main advances are summarized in Table 1. Recently, with the emergence of the COVID-19 pandemic, GO application as antivirals has broadly increased.…”
Section: Antiviral Properties Of the Masksmentioning
confidence: 99%
“…Second, the sensors and their components need to maintain sterility. Antimicrobial nanocomposites offer a promise to this end; [ 9 ] however, flexible, glove‐integrated antimicrobial sensors remain to be introduced. In fact, concerns about sterility may be avoided if the sensors are still functional even when mounted on a glove underneath a second sterile glove worn on top.…”
Section: Introductionmentioning
confidence: 99%